Hubungan Polusi Laut dan Perubahan Iklim terhadap Sebaran Resistensi Antibiotik - Adelia Ikrima; Nadia Nadia; Nor Latifah (Inovasi Kesehatan Global, 2025)
Antibiotic resistance (AR) has emerged as a critical global public health concern, particularly due to the spread of antibiotic-resistant bacteria (ARB) and their genes in natural environments. The oceans, which host diverse ecosystems and serve as major food sources, are increasingly affected by ARB pollution, originating from human, agricultural, and industrial activities. Simultaneously, climate change (CC) exacerbates the situation by raising ocean temperatures, lowering pH, and altering marine biodiversity—creating optimal conditions for bacterial survival and gene transfer. This review explores the interconnectedness between ocean pollution and CC and how both factors influence the distribution and persistence of ARB and antibiotic resistance genes (ARGs) in marine ecosystems. Through a systematic literature review of 174 peer-reviewed articles, the study highlights how anthropogenic pollutants—especially antibiotics, heavy metals, and plastics—contribute to resistance emergence. Furthermore, it discusses the transmission pathways from pollution hotspots (e.g., hospitals, agriculture, wastewater) to the oceans. The One Health (OH) strategy is presented as a comprehensive solution to address the environmental, human, and animal health risks posed by antibiotic pollution. This paper serves as a basis for future research into surveillance, mitigation, and policy interventions for controlling AR in marine environments.